Sociāli emocionālās attīstības veicināšana pirmsskolas izglītības iestādē 3-4 gadus veciem bērniem - Āboltiņa, Karīna (Latvijas Universitāte, 2021)
Darba nosaukums: Sociāli emocionālās attīstības veicināšana pirmsskolas izglītības iestādē 3-4 gadus veciem bērniem Darba autore: Karīna Āboltiņa Pētījuma mērķis: Izpētīt sociāli emocionālās attīstības veicināšanu pirmsskolas izglītības iestādē 3-4 gadus veciem bērniem. Pētījuma objekts: Sociāli emocionālās attīstības veicināšana. Darbs sastāv no 2 nodaļām. Pirmajā darba nodaļā, analizējot pedagoģijas un psiholoģijas zinātnes teorijas, tiek apskatīts sociāli emocionālās attīstības jēdziena skaidrojums, kā arī raksturota sociāli emocionālās attīstības veidošanās 3 – 4 gadus veciem bērniem. Otrajā nodaļā, pētījuma empīriskajā daļā, veikts pētījums par sociāli emocionālās attīstības veicināšanu 3 -4 gadus veciem bērniem pirmsskolas izglītības iestādē: anketēšanas, novērojuma un eksperimentālas darbības datu analīze. Darba noslēgumā ir apkopoti secinājumi. Atslēgvārdi: Sociāli emocionālā attīstība, bērnu vecumposma attīstība, 3 – 4 gadi

Work title: Promoting socially emotional development in pre-school education for 3-4 year-olds Work author: Karīna Āboltiņa Purpose of research: To explore the promotion of socio-emotional development in preschool education institution for children 3 – 4 years old. Subject matter of the research: Promoting socially emotional development. Tasks: • To analyse pedagogies and psychology science theories on socio-emotional development. • Describe the development of socio-emotional development in children aged 3-4 years. • Theoretically and practically study the possibilities for promoting socio-emotional development for children aged 3 to 4 years in preschool education institution. Research methods: • Theoretical methods - theoretical analysis of literature. • Empirical – observation, negotiation,questionnaire and analysis of the data obtained Research base: Riga “X” preschool educational institution. Amount of work: The first chapter of the work deals with the interpretation of the concept of socio-emotional development in pedagogies un psychology science theories and describes the development of socio-emotional development for children aged 3 – 4 years. The second chapter of the work, the practical part of the study was a study of the promotion of social emotinal development for children aged 3-4 yeras in preschool education institution. Key words: Social - emotional development,child development, 3-4 years.
Promoting socially emotional development in pre-school education for 3-4 year-olds
Keywords: Pedagoģija; Sociāli emocionālā attīstība; Bērnu vecumposma attīstība; 3-4 gadi; Attīstība